Frequency and timing of other primary cancers in patients with chronic lymphocytic leukemia (CLL): a 17-year longitudinal study. Issue 5 (16th April 2022) - Akhtar, Othman Salim; Groman, Adrienne; Singh, Anil; Ghione, Paola; Lund, Ian; Hernandez-Ilizaliturri, Francisco J.; Torka, Pallawi
Abstract: Patients with chronic lymphocytic leukemia (CLL) are known to be at a higher risk of developing other primary cancers (OPC). Identifying latency and risk factors associated with OPCs in CLL is of interest as select patients may potentially benefit from early treatment of CLL with targeted therapies to improve immune surveillance. In this single-center retrospective study, 16.9% of 969 patients with CLL were diagnosed with an OPC. Interestingly, 44% of OPCs were diagnosed prior to the CLL diagnosis, including 30% that were diagnosed >1 year prior. This included a majority of genitourinary cancers and melanoma skin cancers. Patients with CLL and an OPC were older than pts with no OPCs but no other risk factors for developing OPCs were identified. Our data suggest that not only are patients with CLL at higher risk of developing OPCs and warrant appropriate cancer surveillance, but the risk also precedes CLL diagnosis by several years.